Essays in asset pricing - SONG, Wanshan (Institutional Knowledge at Singapore Management University, 2019)
My dissertation centers on two areas related to market microstructure. First, the role of retail traders, or the information they have, for financial markets. I use retail short selling as an example to narrow down the topic and study their trading patterns and trading strategies. Second, the role of passive indexers such as index funds or ETFs, for financial markets. I am trying to analyze the channels through which the nominally uninformed traders have influences on the return and market quality of the underlying stocks. In Chapter 2, I study retail short sellers. It is interesting to paint retail short sellers in a positive light, because most of the literature assume that retail investors are noise traders and less likely to take short selling positions. First, by using a novel short sell transaction data from 2010 to 2016, this paper is the first to provide a comprehensive sample of short selling initiated by retail investors. I find that retail short selling is not limited, which takes up around 11% of retail trading. Second, using this sample, I find that retail short selling can predict negative stock returns. A trading strategy that mimics weekly retail shorting earns an annualized riskadjusted value-(equal-) weighted return of 6% (12.25%). Their predictive ability is beyond that coming from overall retail investors as a group or from off-exchange institutional short sellers. Third, my results suggest that retail short sellers can profitably exploit public information, especially when it is negative. Retail short sellers also tend to be contrarians who provide liquidity when the market is one-sided due to (institutional) buying pressures. Therefore, this paper broadens our understanding on the heterogeneity of short sellers, sheds new light on the strategies of informed traders, and complements a growing literature about the informativeness of retail investors. In Chapter 3, I am mainly working on passive investing. Since the decision to buy or sell stocks is often directed by broader fund flows and rebalancing and not typically by stock fundamentals, we construct proxies for the two sources of trading in passive investments: one is proportionally flow-induced trading; the other is disproportionally index rebalancing. Next, we consider systematic information and provide three measures of price efficiency: price delay, variance ratio, and return synchronicity. We find that indexing significantly increases price efficiency, especially the market- (industry-) wide information. There are two related channels that drive this positive effect. First is through arbitrage: passive investing causes price discrepancies and decreases arbitrage costs, which in turn increases the speed with which systematic information is incorporated into stock prices. The second driver of the positive effect is through short selling: stocks that are added to indexes increase the available lendable shares, which reduces the cost of short selling and thus makes the incorporation of (negative) information into price faster. Overall, this paper establishes and explains the link between indexing and market quality. In Chapter 4, I am instead starting from passive holding. Especially, index funds right now are the largest stake holders of most SP500 stocks, and they are regarded as long-term holders. It is therefore important to see how the fund managers are motived to monitor, vote, and engage with firm-level governance and long-term performance. We find that the stocks with the longest passive holding indeed outperform. We stress that the active monitoring role of passive funds contributes to long-term value creation.